Adolescent self-detection of type 2 diabetes mellitus in Indonesia: an integrative literature review of risk identification and screening tools - Novita Verayanti Manalu; Esti Yunitasari; Sriyono Sriyono; Nursalam Nursalam; Hurun Ain; Pipit Feriani; Candra Kusuma Negara; Ahmad Masfi; Siti Kotijah (Pediomaternal Nursing Journal, 2026)
Introduction: The prevalence of diabetes mellitus among adolescents in Indonesia has increased dramatically, rising nearly 70-fold between 2010 and 2024. Despite this trend, evidence on adolescent self-detection remains limited. This study aims to synthesize global evidence on adolescents' ability to identify high-risk and asymptomatic individuals for T2DM and to determine appropriate tools for early self-detection, with interpretation in the Indonesian context. Methods: An integrative literature review was conducted following the framework of Whittemore and Knafl and PRISMA 2020 guidelines. Four databases (Scopus, PubMed, Web of Science, and Google Scholar) were searched (2011–March 2025). A total of 785 records were identified, of which 23 studies met the inclusion and quality criteria. Results: No study specifically addressed adolescent self-detection tools in Indonesia. However, key domains for early detection were identified, including anthropometric indicators, lifestyle behaviors, family history, and clinical signs. The oral glucose tolerance test (OGTT) showed the highest sensitivity, while HbA1c and fasting plasma glucose were more feasible for routine use. Non-invasive measures such as body mass index and validated risk scores (e.g., IDRS and FINDRISC) were suitable for community and school-based screening. Conclusion: Early detection of T2DM in adolescents requires an integrated approach combining risk profiling, observable indicators, and accessible screening tools. Strengthening adolescent self-detection through age-appropriate and practical instruments may facilitate timely prevention and reduce the growing burden of diabetes. Keywords: adolescents; early detection; risk assessment; self-screening; T2DM